Y-4=-3(x+6)

Simple and best practice solution for Y-4=-3(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-4=-3(x+6) equation:


Simplifying
Y + -4 = -3(x + 6)

Reorder the terms:
-4 + Y = -3(x + 6)

Reorder the terms:
-4 + Y = -3(6 + x)
-4 + Y = (6 * -3 + x * -3)
-4 + Y = (-18 + -3x)

Solving
-4 + Y = -18 + -3x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + Y = -18 + 4 + -3x

Combine like terms: -4 + 4 = 0
0 + Y = -18 + 4 + -3x
Y = -18 + 4 + -3x

Combine like terms: -18 + 4 = -14
Y = -14 + -3x

Simplifying
Y = -14 + -3x

See similar equations:

| 20x+200=x | | (3x+2)(x-3)=7x-1 | | 4x^2+2x=5 | | f/9-138=156 | | 16t^2-2t-3=0 | | (X-2)/6=(x+10)/8 | | -7-3x=8 | | 23/10=6-m | | x=2x+200 | | 6-m=23/10 | | 0.35/100x100 | | 21-4n=5 | | 8Y+3=6Y-13 | | -m^2-8m=16 | | -3m^2+27m=0 | | -24+6x=30 | | 5x+22-3x=45 | | 15-x/2=x/3 | | 5x+22-3x= | | 12b^2+25b+1=0 | | 12x=-3(-5+x) | | 2x^2+12x+24/2=0 | | 2(2x+3)=3(x+2)+x | | P=7L+7W | | 2x^2+12x+24=0/2 | | -(m-1)=13-4m | | 3/8=-1/2p | | 10k-4k+2k-6k=20 | | 14.2z+11.9-9.6z-15.2= | | 10k-4k+6k=20 | | 550x=1680x | | -(12-5f)=3 |

Equations solver categories